The Effect of Nutrition Education Based on Local Foods on Mothers’ Knowledge and Anthropometry of Malnutrition Children Aged 6 to 21 Months - Gumelar, Wahyu Retno; Tangpukdee, Juraporn (The Malaysian Journal of Nursing (MJN), 2022)
Background: Child’s nutrition is an important factor in child’s development, growth, and immunity particularly in the first two years of life. Lack of nutrition about complementary foods (quantity and quality) during this period also causes malnutrition. Methods: A quasi-experimental pre-post test design with single group research was aimed to study the effect of Local foods education on mother knowledge and anthropometry of child. Paired-T tests were used to analyze the effects of local foods education on mother knowledge and child anthropometry 6-21 months. Results: This study showed the mean differences of mother knowledge 10.91 (p=0.000), anthropometry of child weight-for-age 0.20 (±0.54) (p=0.037), height/length-for-age 0.01 (±0.23) (p=0.711), weight-for-height/length 0.31 (±.76) (p=0.025), head circumference-for-age 0.27(±.43) (p=0.001), and chest circumference-for-age 9.12(±10.11) (p=0.000). All variables had a significant effect after local foods education was provided (p<0.05), except height-for-age which showed p>0.05. Conclusion: The results revealed the effectiveness of the local food education to mothers with video recording and booklets. This intervention significantly increased mother's knowledge and anthropometry of child except height/length-for-age in the first month follow up.